From Primary to Secondary Norms: Investigating Internal Deviation in Joseph Conrad’s The Secret Agent - Tanto, Trisnowati; Tanusy, Jeanyfer (Insaniyat: Journal of Islam and Humanities, 2024)
A writer’s distinctive narrative style, often referred to as their primary norm, shapes their consistent use of language. However, deliberate deviations from this norm can serve significant literary purposes. These deliberate deviations are termed as their secondary norm. This change of language style is believed to hold a specific intention on the part of the writer. This research aims to investigate Joseph Conrad’s instances of internal deviation in his novel The Secret Agent, and how these deviations contribute to the literary effects of the novel. Conrad’s primary norm is characterized by a sentence-complexity style, while his secondary norm involves a shift towards a sentence-simplicity style. To clarify these norms, the study employs the clause complexes theory within the framework of Halliday’s Systemic Functional Linguistics. Employing a descriptive qualitative research approach along with a library research method, this study collects and analyses data to uncover the instances of deviation and explore their literary implications. By examining Conrad’s intentional internal deviations, this research seeks to describe the underlying motives and the impact of these deviations on the overall reading experience of The Secret Agent. Through this investigation, it is found out that Conrad’s use of sentence simplicity style contributes to the novel’s literary effects, namely building the foreshadowing and suspense, developing the character, and setting the atmosphere of the novel.